2007
DOI: 10.1002/iroh.200510954
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Leaf Breakdown of Three Native Tree Species in a Slowly‐Flowing Headwater Stream in the Colombian Andes

Abstract: The dynamics of leaf breakdown in a headwater Colombian stream were evaluated for the native tree species Myrsine guianensis, Cupania latifolia and Nectandra lineatifolia using coarse and fine mesh litter bags. Ten bags of each species (five of each mesh size) were retrieved from the stream at 1, 8, 15, 30, 60 and 120 days. k values ranged from 0.0008 to 0.0058 day -1 and density of macroinvertebrates from 35 to 55 individuals per leaf bag, peaking at day 8. Myrsine guianensis degraded more rapidly than the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
3
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
(45 reference statements)
2
17
3
8
Order By: Relevance
“…Otra tendencia interesante registrada en estudios de quebradas protegidas de los Andes colombianos (10,25), es que a pesar de la dominancia numérica de los colectores, los fragmentadores son más importantes en términos de biomasa por tratarse de individuos de mayor tamaño. Por esta razón sería recomendable evaluar la biomasa relativa de los grupos dietarios de la cuenca del río La Vieja, con el fin de establecer si se mantiene esta condición, que confirma la relevancia ecológica de los fragmentadores.…”
Section: Discussionunclassified
“…Otra tendencia interesante registrada en estudios de quebradas protegidas de los Andes colombianos (10,25), es que a pesar de la dominancia numérica de los colectores, los fragmentadores son más importantes en términos de biomasa por tratarse de individuos de mayor tamaño. Por esta razón sería recomendable evaluar la biomasa relativa de los grupos dietarios de la cuenca del río La Vieja, con el fin de establecer si se mantiene esta condición, que confirma la relevancia ecológica de los fragmentadores.…”
Section: Discussionunclassified
“…Several studies have suggested that tropical shredders are scarce (Dobson et al, 2002;Rueda-Delgado et al, 2006;Wantzen and Wagner, 2006;Gonc¸alves et al, 2007), while others have shown the opposite (Cheshire et al, 2005;Wright and Covich, 2005;Chara´et al, 2007;Camacho et al, 2009;Rı´os-Touma et al, 2009;Yule et al, 2009). A recent global study has demonstrated not only that shredder diversity increases with latitude (Boyero et al, 2011b) but also that variability in shredder abundance and diversity within the tropics is higher than within temperate areas (Boyero et al, 2011c).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some studies have reported the importance of the activity of macroinvertebrate shredders in tropical streams (YULE, 1996;CHESHIRE et al, 2005;BOYERO et al, 2006;CHARA et al, 2007;RÍOS et al, 2009;YULE et al, 2009). In this context, TOMANOVA et al (2006) and CAMACHO et al (2009) indicated that this function has been underestimated due to the deceptive assumption that taxa in the tropics belong to the same feeding groups as in temperate rivers.…”
Section: Introductionmentioning
confidence: 69%
“…For example, in Australian streams, CHESHIRE et al (2005) based on gut contents analysis, found that despite of many invertebrates were generalist in their diets, shredders were an important component of the assemblages, especially in biomass and richness taxa. Also, CHARA et al (2007) evaluated the decomposition of three native plant species in a river headwater in the Colombian Andes indicating that shredders represent an important role in litter breakdown. Furthermore, RÍOS et al (2009) reported a shredder activity of 35% (by gut content analysis) on the basis of the relative density of 11 most abundant taxa in a river headwater in the highlands of Ecuador.…”
Section: Introductionmentioning
confidence: 99%